Impact of Bank Liquidity and Macroeconomic Determinants on Profitability of Commercial Banks in Bangladesh - Lalon, Raad Mozib; Anika Afroz; Tasneema Khan (International Journal of Economics and Financial Issues, 2023)
This paper aims at investigating the relationship between profitability and liquidity of the State-Owned Commercial Banks of Bangladesh. An important motive of this study is to provide valuable insights into how liquidity influences profitability. There are various research papers on liquidity exposure and the profitability relationship of banks in Bangladesh. But those researches are separately conducted for conventional or Islamic banks or there is a comparative analysis of both banks. But there is little research on the state-owned banking industry. During the Pandemic the banking industry of Bangladesh was affected severely in respect of liquidity risk and it also affected its profitability. There is no recent paper focused on this study. So, this study will try to identify the significant factors that affect the liquidity of a bank and its profitability. In this regard, 10 years’ data from Annual Report of the State-Owned Commercial Banks and macroeconomic data from Bangladesh Bank website and several journals have been collected from 2012-2021. This study primarily aims at exploring the liquidity-profitability relationship using econometric model. Loan to Deposit ratio is used measuring liquidity of a bank. Other control variables Loan Loss Provision to Total Asset (LLPTA) for credit risk, Equity to Total Asset (EQTA) for capital efficiency, Operational expense to Total Asset (OPEXTA) for operational efficiency, Total Asset (TA) for Bank size, Non-performing Loan (NPL) for asset quality, Gross Domestic Product (GDP) for economy size, Inflation (INF) for consumer price index, Interest Rate (INT) for opportunity cost, and the Unemployment rate for measuring labor force. The major finding of this study show that there is a significant positive relationship between liquidity risk and profitability. Among bank-specific variables credit risk, capital efficiency, and bank size have a significant relationship with Profitability which also supports the theory. Macroeconomic variables like interest rate, inflation rate, and GDP have a significant relationship with profitability which also supports the theory. Here BDBL and BASIC should have maintained the liquidity standard mentioned by Bangladesh Bank and BIS to mitigate their liquidity crisis. This study also shows that there is no severe effect of the COVID pandemic on the State-Owned Commercial Banks of Bangladesh. The findings of this study will provide valuable insights for banks and regulators to make informed decisions regarding risk management, liquidity decision, capital allocation, and strategic planning.